A case of linear lichen planus - Kökçam, I; Ozercan, IH (Japanese Dermatolgical Assoc, 2005)
Linear lichen planus (LLP) is a very rare form of lichen planus (LP) characterized by a linear distribution of the lichenoid lesions. It usually follows the lines of Blaschko with unilateral involvement. We report such a case of LLP. A 50-year-old man presented with slightly pruritic, linear, violaceous, papular lesions on the right side of his jaw. A biopsy specimen demonstrated the typical histology of LP. Based on the clinical and pathological findings, the diagnosis was LLP.
Keywords: linear lichen planus; buccal mucous lesions